Simulação dinâmica do processo de destilação de bioetanol em simulador baseado em equações (EMSO) - Silva, José Izaquiel Santos da (2012)
Distillation of hydroalcoholic mixtures that result from the fermentative route of production of ethanol has been widely studied. Nonetheless, three points have not deserved special attention yet: the industrial fermentation intrinsic variability; the changes on the feed stream of the columns caused by the mixing of 1st (1G) and 2nd (2G) generation wines in the same biorefinery; and the alteration of the level in the buffer vat throughout the operation of the industrial plant. The two first aspects result in changes of the concentration of ethanol and other fermentation by-products, such as isoamyl alcohol in the buffer tank. The third aspect alters the flow impelled by the feed pumps and, consequently, changes the outlet temperature of the K heat exchanger (i.e. of the first column feed stream). In this work, the EMSO simulator (Environment for Modeling, Simulation and Optimization) was used to study transient perturbations of the columns operation, and the effect of wine composition in the buffer vat that will be pumped for distillation, with aid of a column model representing the distillation train A-A1-D. Reboiler and condenser temperatures and levels are controlled by PID loops, and the dynamic model of the tray column includes correlations (already implemented in EMSO) for liquid holdup, pressure drop in the tray, among other aspects. The gamma-phi approach, using UNIFACDortmund equation for the liquid phase non-ideality and SRK model for the vapour, was used to represent vapor-liquid equilibrium (VLE). Firstly, the dynamics of distillation of ethanol-water and ethanol-water-isoamyl alcohol mixtures was simulated, up to steady state. The EMSO steady-state results were very similar to Aspen-Pus® (7.3) simulations. Following, in order to closer represent the complexity of the real situation, a model of the centrifugal pump plus tabulation was inserted in EMSO, integrated to the K heat exchanger (that regenerates the energy of vinasse, pre-heating the column feed) and to the column itself. The main conclusions were: the presence of isoamyl alcohol influenced somehow the temperature and molar fractions transient profiles in the column, but the composition of the top stream was not sensibly affected. Changes of the liquid level in the buffer vat during the operation, following loadunload cycles, caused periodic perturbations in the system output variables (flows, temperatures and mol fractions of the process outflow), whose amplitude could be absorbed by the control system. Step perturbations in the buffer vat were simulated, with consistent responses, as assessed by the system global mass balance. Mixing wines with lower alcoholic contents, as the ones coming from the 2G process, causes effects that are dumped after one load-reload cycle of the vat. In long term, model responses indicate that, kept the reflux ratio and the top and bottom conditions in the column, the system gradually achieves stable operation points.